Oxidative additions of alkynyl/vinyl iodides to gold and gold-catalyzed vinylation reactions triggered by the MeDalphos ligand. Issue 22 (5th May 2021) - Rodriguez, Jessica; Tabey, Alexis; Mallet-Ladeira, Sonia; Bourissou, Didier
Abstract : The hemilabile Ad2 P( o -C6 H4 )NMe2 ligand promotes fast, quantitative and irreversible oxidative addition of alkynyl and vinyl iodides to gold. Abstract : The hemilabile Ad2 P( o -C6 H4 )NMe2 ligand promotes fast, quantitative and irreversible oxidative addition of alkynyl and vinyl iodides to gold. The reaction is general. It works with a broad range of substrates of various electronic bias and steric demand, and proceeds with complete retention of stereochemistry from Z and E vinyl iodides. Both alkynyl and vinyl iodides react faster than aryl iodides. The elementary step is amenable to catalysis. Oxidative addition of vinyl iodides to gold and π-activation of alkenols (and N -alkenyl amines) at gold have been combined to achieve hetero-vinylation reactions. A number of functionalized heterocycles, i.e. tetrahydrofuranes, tetrahydropyranes, oxepanes and pyrrolidines were obtained thereby (24 examples, 87% average yield). Taking advantage of the chemoselectivity for vinyl iodides over aryl iodides, sequential transformations involving first a hetero-vinylation step and then a C–N coupling, a C–C coupling or an heteroarylation were achieved from a vinyl/aryl bis-iodide substrate.